2006
DOI: 10.1185/030079906x96245
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of symptom-free days in generalized anxiety disorder

Abstract: SFDs differentiate between active treatment and placebo in clinical trials and may be an appropriate measure of treatment effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…By contrast, in clinical studies, response and remission treatment outcomes correlate highly; by definition, patients achieving remission will also have achieved a response. 22 36 39 The possible reasons for the lack of correlation in our analysis are that our approach compared response and remission rates across a broad range of clinical studies, in varying settings, and was conducted in groups of patients with differing severity of symptoms and undergoing treatment with varying regimens. As a result, the data informing our meta-analysis did not represent a discrete or continuous population and some studies included in our analysis reported response rates only, with no remission data.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in clinical studies, response and remission treatment outcomes correlate highly; by definition, patients achieving remission will also have achieved a response. 22 36 39 The possible reasons for the lack of correlation in our analysis are that our approach compared response and remission rates across a broad range of clinical studies, in varying settings, and was conducted in groups of patients with differing severity of symptoms and undergoing treatment with varying regimens. As a result, the data informing our meta-analysis did not represent a discrete or continuous population and some studies included in our analysis reported response rates only, with no remission data.…”
Section: Discussionmentioning
confidence: 99%
“…Second, measures of clinical effectiveness employed in our model include time (i.e., weeks) with no or minimal anxiety in addition to QALYs. While use of QALYs allows comparisons with findings from pharmacoeconomic evaluations of interventions for other medical conditions, use of “time without symptoms” may best reflect favorable clinical outcomes from the patient’s perspective [1822]. We believe that our study is the first to report estimates of the cost-effectiveness of pharmacologic treatment of GAD using such a measure.…”
Section: Discussionmentioning
confidence: 99%
“…While (to the best of our knowledge) these categorizations have not been validated clinically, they have been employed by others [16, 17]. The value of using time without symptoms to compare treatments of chronic symptomatic diseases has long been recognized in a variety of medical conditions, including pain, depression, and epilepsy [1822]. …”
Section: Methodsmentioning
confidence: 99%
“…Following the characteristics of patients included in most clinical trials, the model considers that before implementation of any pharmacotherapeutic option all patients have either moderate or severe anxiety. Clinical gains are achieved whenever disease management allows subjects to be classified in less severe categories, following the rationale of valuing time without or with lighter symptoms that was already applied in economic evaluations of medical conditions as pain, depression and epilepsy [11-15]. …”
Section: Methodsmentioning
confidence: 99%